Patient-Centred Health Care Achieving Co-ordination, Communication and Innovation - Keating, M.; McDermott, A.; Montgomery, K.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
There are four core themes developed in this book which deal with critical issues, models, theories and frameworks. These expound understandings of patient centred care and the processes, practices and behaviours supporting its attainment: conceptions and cultures of patient-centred care, coordination, communication, innovation.
Keywords: Management; Organization; Planning; Public health; Economic development; Business ethics; Social policy; Management; Organization; Public Health; Development Studies; Business Ethics; Social Policy